Consumer perceptions of beef healthiness: results from a qualitative study in four European countries - de Barcellos Marcia D; Verbeke Wim; Van Wezemael Lynn; Scholderer Joachim; Perez-Cueto Federico (BMC, 2010)
Abstract Background Consumer perception of the healthiness of beef is an important determinant of beef consumption. However, little is known about how consumers perceive the healthiness of beef. The aim of this study is to shed light on the associations between beef and health. Methods Eight focus group discussions were conducted in four European countries (France, UK, Germany, Spain), each consisting of seven to nine participants. A content analysis was performed on the transcripts of these discussions. Results Although beef was generally perceived as healthful, focus group participants expected positive as well as negative effects of beef consumption on their health. Labelled, branded, fresh and lean beef were perceived as signalling healthful beef, in contrast with further processed and packaged beef. Consumers felt that their individual choices could make a difference with respect to the healthiness of beef consumed. Focus group participants were not in favour of improving beef healthiness during processing, but rather focussed on appropriate consumption behaviour and preparation methods. Conclusions The individual responsibility for health implies that consumers should be able to make correct judgements about how healthful their food is. However, the results of this study indicate that an accurate assessment of beef healthiness is not always straightforward. The presented results on consumer perceptions of beef healthiness provide insights into consumer decision making processes, which are important for the innovation and product differentiation in the European beef sector, as well as for public health policy decisions related to meat consumption in general and beef consumption in particular.